Indigenous People and COVID-19 in Peru: Health Crisis and Structural Deficiencies - Orcotorio Figueroa, Rodrigo Walter (2022)
The COVID-19 pandemic is an event of large and complex proportions. The Peruvian government tried for countless times to deal with its consequences during the first year of the crisis. However, due to the social and economic conditions of most of the population, these attempts turned out to be unsuccessful and in specific cases only exacerbated the effects of the pandemic. In that regard, native communities, and generally indigenous peoples, suffered from structural public service lacks in terms of access to drinking water and health that COVID-19 oversaw revealing. Belated responses of the central government and preferences for economic reactivation revealed a serious contradiction between priorities in managing the crisis in the Amazonian territories. This paper addresses these structural conditions referred to public services, especially those related to access to drinking water and health in native communities. It additionally analyzes legislative and administrative measures implemented to protect native communities and strengthen their capacities against COVID-19.  All this leads to an inquiry on the real flaws and deficiencies of the national proposal for economic reactivation and the problem experienced by these communities in the first year of the crisis.